DISSOLUTION PROFILE OF AMBROXOL HCl TABLET WITH ADDITIONAL VARIATIONS OF LUDIPRESS® AND LACTOSE USING THE DIRECT PRESS METHOD - MUSTARICHIE, RESMI; GOZALI, DOLIH; PRIAMBODO, DRADJAD (International Journal of Applied Pharmaceutics, 2020)
Objective: The drug will provide a therapeutic effect when dissolved so that it is easily absorbed. The process of dissolving drugs is called dissolution. Additional substances contained in pharmaceutical preparations, one of which serves to accelerate the solubility of active substances. The aim of this study was to obtain a comparative composition of Ludipress® and lactose additives suitable for producing ambroxol HCl tablets that met the ambroxol acceleration ambroxol in the body. Methods: Ambroxol HCl tablets were made by direct pressing method. For research purposes, 4 formulas with variations of Ludipress® and Lactose were designed. The tablet was then evaluated, which includes uniformity in weight, diameter, thickness, hardness, friability, disintegration time, and dissolution. Data obtained in the analysis using the perfect random block design method (DBAS) with α = 0.05 where blocks and groups were used. Results: From the results of the Mass Printing Evaluation of Tablets, it was found that the four formulas that were designed met the resting angle, flow rate, real density, compressed density, and compressibility met existing requirements. The results of evaluation tablets, which included uniformity of weight, uniformity of size, hardness, friability, disintegration time, and dissolution test, were found that only F1 formula did not meet uniformity requirements. All four formulas meet the Indonesian pharmacopeia requirements for time of violence, fragility and disintegration. The dissolution test results showed that in the 45-minute test each percent dissolved concentration of the active substance for F1, F2, F3, and F4 was 58.77974, 66.91104, 80.09946, and 64.02293 suggesting only the F3 formula fulfilled the dissolution requirements according to European Pharmacopoeia which stated that the concentration of dissolved active tablets should not be less than 75% during the 45-minute test. Conclusion: The formula that met the solubility requirements consisted of an additional 69% Ludipress® and 10% lactose with a solubility value of 80.09%.